USING CARTOONS AND ANIMATED STORIES TO DEVELOP LISTENING AND COMPREHENSION SKILLS - Rixsitillayeva Muxlisa Lutfulla qizi; Matenova Feruza Maxamatali qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This article explores the effectiveness of using cartoons and animated stories to enhance listening and comprehension skills in language learners. By integrating visual elements with spoken language, cartoons provide an engaging and dynamic approach to language acquisition. The study examines how both passive and active listening techniques, facilitated by animated content, help learners improve their ability to understand and retain language. The findings reveal that repeated exposure to animated stories significantly enhances vocabulary recognition, listening comprehension, and retention. Additionally, cartoons expose learners to natural speech patterns, including intonation and conversational tone, which are often difficult to grasp through traditional methods. The results suggest that cartoons and animated stories are valuable tools for learners of all ages and proficiency levels, offering a fun, interactive way to strengthen essential language skills. The study advocates for the incorporation of animated content into language learning programs to create a more engaging and effective educational experience.